Analisis Pengukuran Kinerja Perusahaan Dengan Konsep Kartu Skor Berimbang - Sri Laksmi Pardanawati; Rukmini Rukmini; Muhammad Luthfi Nur Fatyasin (ITB AAS INDONESIA, 2020)
ABSTRACT This study aims to determine the effect of partially and simultaneously financial perspective, customer perspective, internal business perspective, growth perspective and learning on the performance of PT Parama.This research uses a quantitative descriptive approach, with a sample of 33 respondents. Primary data were obtained from questionnaires filled out with questionnaires that had previously been tested for validity and reliability. Data analysis techniques using multiple linear regression analysis. The research results partially obtained financial perspective variables partially affect the performance of PT Parama's company, customer perspective variables partially affect PT Parama's corporate performance, internal business process perspective variables partially affect PT Parama's company performance, growth perspective and learning variables influence partial to the company's performance of PT Parama. The results simultaneously obtained financial perspective, customer perspective, internal business perspective, learning perspective and growth simultaneously influence the performance of the company PT Parama Keywords:Balanced Scorecard, financial perspective, customer perspective, internal business process perspective, learning and growth perspective, corporate performance